#### Answer

a. $3a-2$
b. $-3x-2$
c. $3x+3h-2$

#### Work Step by Step

We are given that $P(x)=3x-2$
$P(a)=3(a)-2=3a-2$
$P(-x)=3(-x)-2=-3x-2$
$P(x+h)=3(x+h)-2=3x+3h-2$

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

a. $3a-2$
b. $-3x-2$
c. $3x+3h-2$

We are given that $P(x)=3x-2$
$P(a)=3(a)-2=3a-2$
$P(-x)=3(-x)-2=-3x-2$
$P(x+h)=3(x+h)-2=3x+3h-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.